A Comparative Novel Method of Antifungal Susceptibility for Malassezia furfur and Modification of Culture Medium by Adding Lipid Supplement - Kumar1, S. Srivastava1, A. Dikshit1, A. Pandey1, and K. Bajaj2, Amit K. Tiwari1*, Rohit K. Mishra1, A. (Journal of Phytology, 2011)
Introduction of new antifungal compounds has increased the demand for method of in vitro testing. The present study has proposed a new method of studying antifungal activity of different compounds by using 96 well plates. The infection by different species of Malassezia is quite common in tropical country like India. Malassezia being a eukaryote, the treatments against it may also adversely affect the patient. Hence, as an alternative, cheap, affordable, ecofriendly, botanicals may be used. In this background, a comparative study on the efficacy of synthetic ingredients (on the basis of their performance in the market) and botanicals was carried out in-vitro against Malassezia furfur (MTCC 1765).Evaluation of Minimum Inhibitory Concentrations (MICs) of two standard antifungal drugs (Ketoconazole and Fluconazole) available in the market against Malassezia furfur and their comparison with botanicals was done using broth microdilution method recommended by Clinical Laboratory Standard Institute (CLSI) with slight modifications. The present work is also an attempt to standardized culture medium for growing Malassezia species by overlay of sterile cotton seed oil with principal medium. Cotton seed oil can be used as supplement with principal medium for best growth of Malassezia. Keywords: Botanicals, Malassezia furfur, Minimum Inhibitory Concentrations, Synthetics <span style="font-weight: normal; font-size: 7pt; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Amit Kumar Tiwari et al. A Comparative Novel Method of Antifungal Susceptibility for Malassezia furfur and Modification of Culture Medium by Adding Lipid Supplement. J. Phytol 3/3 (2011) 44-52.